THE MULTI-CHANNEL DIGITAL DIAGNOSTIC METHOD OF RELAY - Razghonov, O. P.; Adreievskyi, O. V.; Bondarenko, B. M.; Bezrukavyi, D. O.; Zhuravlev, O. Yu. (Science and Transport Progress, 2007)
The multichannel digital method diagnostics of relay consists in the use of experimentally findings, for the calculation of parameters of examinee relay. During registration of dynamic descriptions parallel on all channels, analog-to-digital treatment of results is produced, by the method of comparison with the admittances stopped up in memory of computer and is drawn conclusion about the good condition of device.